A gestão integrada de resíduos sólidos urbanos - perspectiva ambiental e económico-energética The urban solid waste integrated management environmental and economic-energetic perspective - Jaime Filipe Borges Puna; Bráulio dos Santos Baptista (Química Nova, 2008)
The importance of urban solid waste integrated systems is characterized by the several components of these systems, which are, basically, formed by physical, chemical and biological methods. This article, characterizes these methods and, which is also important, identifies the several and potential environmental impacts of those techniques. It's also extremely important to make a study of the economic rentability of those infrastructures and, also, characterize the quantitative energetic contributions of some components of these systems. This study was analysed and their results are presented in this article.